Water-dispersible active energy ray-curable composition
Patent Information
- Application Number
- JP2020185352
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-05
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-11-05
AI Technical Summary
【0012】 本発明の水分散型活性エネルギー線硬化性組成物は、硬化性成分として側鎖にアクリロイル基を有する水分散性(メタ)アクリレート重合体を含有するので、側鎖にメタクリロイル基を有する水分散性(メタ)アクリル酸エステル重合体を硬化性成分として含有する従来の硬化性組成物と比較して、硬化性に優れ、他の有機溶媒系硬化性組成物と比較して、環境への影響が少ない。さらに加えて、その硬化物は、引張強度及び伸び等の引張物性、並びに耐候性に優れている。
Smart Images

Figure 0007631740000001 
Figure 0007631740000002 
Figure 0007631740000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-dispersible active energy ray-curable composition which is excellent in curability, is substantially free of organic solvents, has a low environmental impact, and gives a cured product which is excellent in tensile properties and weather resistance. [Background technology]
[0002] An active energy ray-curable composition can be cured by exposure to active energy rays such as ultraviolet rays, visible light, and electron beams for a very short period of time, and has advantages in terms of process, such as a shorter curing time and less energy required for curing, as compared with thermal curing and the like.
[0003] On the other hand, acrylic polymers have the advantage of being superior in tensile properties such as tensile strength and elongation, as well as weather resistance, compared to other polymers.
[0004] As a polymer that satisfies both of these requirements, an acrylic polymer having an acryloyl group in the side chain, so-called acrylic acrylate, is known (see Patent Documents 1 to 3). However, these acrylic acrylates are used in organic solvents, and have the problem of high environmental impact.
[0005] Conventionally, aqueous dispersions of acrylic polymers having (meth)acryloyl groups in their side chains have also been proposed (Patent Documents 4 to 7). However, most of these aqueous dispersions are produced by adding glycidyl methacrylate to a carboxylic acid group-containing polymer, and have a problem in that the curing speed is slow because the side chain is a methacryloyl group. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 58-25365 [Patent Document 2] Japanese Patent Application Publication No. 04-366178 [Patent Document 3] JP 2011-57905 A [Patent Document 4] Japanese Patent Application Publication No. 10-195142 [Patent Document 5] Japanese Patent Application Publication No. 10-195361 [Patent Document 6] Japanese Patent Application Publication No. 10-195371 [Patent Document 7] Japanese Patent Application Publication No. 10-195372 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a water-dispersible active energy ray-curable composition which has excellent curability, is substantially solvent-free, has a low environmental impact, and produces a cured product having excellent tensile properties and weather resistance. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that the above problems can be solved by introducing an acryloyl group into a side chain of a (meth)acrylate polymer, and that a water-dispersible active energy ray-curable composition can be obtained that is excellent in curability, is substantially solvent-free, has a low environmental impact, and provides a cured product that is excellent in tensile properties such as tensile strength and elongation, and in weather resistance, thereby completing the present invention.
[0009] The present invention relates to a water-dispersed active energy ray-curable composition comprising a (meth)acrylate polymer (A) having an acryloyl group in a side chain [hereinafter also referred to as "component (A)"], the component (A) being dispersed in water, wherein the content of an organic solvent in the total amount of the composition is less than 5% by weight. The component (A) is preferably a reaction product of a copolymer (a1) (hereinafter referred to as "copolymer (a1)") having a structural unit derived from a (meth)acrylate monomer (a1-1) having no reactive group and a structural unit derived from a (meth)acrylate monomer (a1-2) having a reactive group, and a compound (a2) (hereinafter referred to as "unsaturated compound (a2)") having a group reactive with the reactive group and an acryloyl group.
[0010] In addition, the (meth)acrylate monomer (a1-2) having a reactive group constituting the copolymer (a1) is preferably a (meth)acrylate monomer having a reactive group selected from the group consisting of an epoxy group, a carboxyl group, a hydroxyl group, and an isocyanate group. Furthermore, the unsaturated compound (a2) is preferably an acrylate oligomer having a glass transition temperature (Tg) of -30 to -90°C. The composition preferably contains component (A) in an amount of 15 to 60% by weight based on the total amount of the composition.
[0011] The active energy ray is preferably an electron beam. Furthermore, the composition of the present invention can be preferably used as a curable composition for a coating agent. The composition is preferably produced by mixing and dispersing the component (A), surfactant (C) and water-soluble organic solvent (D) in water, and then heating the mixture under reduced pressure to adjust the content of the organic solvent in the total amount of the composition to less than 5% by weight. Effect of the Invention
[0012] The water-dispersible active energy ray curable composition of the present invention contains a water-dispersible (meth)acrylate polymer having an acryloyl group in the side chain as a curable component, and therefore has excellent curability compared to conventional curable compositions containing a water-dispersible (meth)acrylic acid ester polymer having a methacryloyl group in the side chain as a curable component, and has less impact on the environment compared to other organic solvent-based curable compositions. In addition, the cured product thereof has excellent tensile properties such as tensile strength and elongation, and weather resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention relates to a water-dispersed active energy ray-curable composition (hereinafter also simply referred to as "composition") comprising a (meth)acrylate polymer (A) [component (A)] having an acryloyl group in a side chain, the composition being formed by dispersing component (A) in water, wherein the content of an organic solvent in the total amount of the composition is less than 5 wt %. The component (A), the water-dispersible active energy ray-curable composition, and the method of use will be described below. In the present invention, the term "(meth)acrylate polymer" means a polymer containing (meth)acrylate as a main component of a structural unit, "(meth)acrylic" means acrylic and / or methacrylic, "(meth)acrylate" means acrylate and / or methacrylate, and "(meth)acryloyl" means acryloyl and / or methacryloyl.
[0014] 1. Component (A) Component (A) is a (meth)acrylate polymer having an acryloyl group in the side chain. As described above, the (meth)acrylate polymer means a polymer containing (meth)acrylate as a main component of the structural units, and means a polymer containing 80 to 100% by weight of (meth)acrylate in all the structural monomer units. Component (A) can be produced by a conventional polymerization method, and the production method is not particularly limited, but a representative example is a polymer in which an acryloyl group is bonded to the side chain of a (meth)acrylate polymer via a suitable atom or atomic group. A preferred example of component (A) is, for example, a reaction product of a copolymer (a1) (hereinafter also referred to as "copolymer (a1)") consisting of a structural unit derived from a (meth)acrylate monomer (a1-1) (hereinafter also referred to as "monomer (a1-1)") having no reactive group and a structural unit derived from a (meth)acrylate monomer (a1-2) (hereinafter also referred to as "monomer (a1-2)") having a reactive group, and a compound (a2) (hereinafter also referred to as "unsaturated compound (a2)") having a group reactive with the reactive group and an acryloyl group. That is, as component (A), a polymer having an acryloyl group bonded as a side chain, obtained by reacting a reactive group of the trunk polymer, copolymer (a1), with a reactive group of an unsaturated compound (a2), is preferred. The copolymer (a1), the unsaturated compound (a2), the method for producing the component (A), and the physical properties of the component (A) will be described below.
[0015] (1) Copolymer (a1) Copolymer (a1), which is the raw material copolymer of component (A), is a copolymer comprising structural units derived from monomer (a1-1) and structural units derived from monomer (a1-2). The monomer (a1-1) and the monomer (a1-2) will be described below.
[0016] (1-1) Monomer (a1-1) The monomer (a1-1) is a (meth)acrylate monomer (a1-1) having no reactive group. Specific examples of the monomer (a1-1) include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tetradecyl (meth)acrylate, and stearyl (meth)acrylate; alicyclic (meth)acrylates such as isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and dicyclopentenyl (meth)acrylate; N-(meth)acryloylmorpholine; acrylamides such as (meth)acrylamide, N-methylolacrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, and N,N-dimethylaminopropyl(meth)acrylamide; and Examples include acrylonitrile and methacrylonitrile.
[0017] (1-2) Monomer (a1-2) The monomer (a1-2) is a (meth)acrylate monomer having a reactive group. The monomer (a1-2) is preferably a (meth)acrylate monomer having a reactive group selected from the group consisting of an epoxy group, a carboxyl group, a hydroxyl group, and an isocyanate group.
[0018] Examples of the monomer (a1-2) having an epoxy group as a reactive group include glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate glycidyl ether.
[0019] Examples of the monomer (a1-2) having a hydroxyl group as a reactive group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and an ε-caprolactone adduct of 2-hydroxyethyl (meth)acrylate.
[0020] An example of the monomer (a1-2) having an isocyanate group as a reactive group is (meth)acryloxyethyl isocyanate, and specific products include "Karenz MOI" and "Karenz AOI" (both trade names, manufactured by Showa Denko).
[0021] Examples of the monomer (a1-2) having a carboxyl group as a reactive group include (meth)acrylic acid, monohydroxyethyl phthalate, ω-carboxy-polycaprolactone (n≒2) monoacrylate, (meth)acryloyloxyethyl succinate, (meth)acryloyloxyethyl hexahydrophthalate, (meth)acryloyloxyethyl phthalate, (meth)acryloyloxyethyl-2-hydroxyethyl phthalate, β-carboxyethyl acrylate, a phthalic anhydride adduct of pentaerythritol triacrylate, a succinic anhydride adduct of pentaerythritol triacrylate, a succinic anhydride adduct of dipentaerythritol triacrylate, and a phthalic anhydride adduct of dipentaerythritol triacrylate.
[0022] (1-3) Preferred copolymerization ratio The copolymerization ratio of monomer (a1-1) and monomer (a1-2) in copolymer (a1) may be set according to the acryloyl group equivalent of the acryloyl group in the target component (A), and the monomer (a1-1) is preferably 5 to 70% by weight, more preferably 15 to 50% by weight, and even more preferably 20 to 40% by weight, of the total of monomer (a1-1) and monomer (a1-2) 100% by weight.
[0023] (1-4) Polymerization method of copolymer (a1) The method for producing the copolymer (a1) before being modified with the unsaturated compound (a2) is not particularly limited, and any known method such as suspension polymerization, emulsion polymerization, solution polymerization, or bulk polymerization can be used. Among these, bulk polymerization and solution polymerization are preferred because the polymer can be easily produced and they do not contain impurities such as emulsifiers.
[0024] (1-4-1) Solution polymerization The solution polymerization method includes a method in which the raw material monomer to be used is dissolved in an organic solvent, a thermal polymerization initiator is added, and the mixture is heated and stirred. When the solution polymerization method is used to synthesize the polymer by radical polymerization, the raw material monomer to be used is dissolved in an organic solvent, a thermal radical polymerization initiator is added, and the mixture is heated and stirred to obtain the polymer. If necessary, a chain transfer agent can be used to adjust the molecular weight of the polymer.
[0025] Examples of organic solvents used in the solution polymerization method include ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as ethyl acetate and butyl acetate; ethers such as propylene glycol monomethyl ether; aromatic hydrocarbons such as toluene and xylene; and aliphatic hydrocarbons such as hexane, heptane, and mineral spirits.
[0026] Examples of the thermal polymerization initiator include azo-based initiators such as azobisisobutyronitrile, azobisisovaleronitrile, azobiscyclohexanecarbonitrile, and azobiscyanovaleric acid; organic peroxides such as t-butyl peroxypivalate, t-hexyl peroxypivalate, dilauroyl peroxide, di(2-ethylhexyl)peroxydicarbonate, di-t-butyl peroxide, and dicumyl peroxide; and hydrogen peroxide-iron(II) salt, peroxodisulfate-sodium hydrogensulfite, cumene hydroperoxide-iron(II) salt, and the like. The proportion of the thermal polymerization initiator used may be appropriately set depending on the target molecular weight. The proportion of the thermal radical polymerization initiator used is preferably 0.1 to 10 parts by weight per 100 parts by weight of the total of all the monomers used.
[0027] (1-4-2) Bulk polymerization Examples of the bulk polymerization method include known methods disclosed in JP-A-57-502171, JP-A-59-6207, JP-A-60-215007, and the like. For example, a method can be mentioned in which a pressurizable reactor is filled with a solvent, and then set at a predetermined temperature under pressure, and a monomer mixture consisting of each monomer and, if necessary, a polymerization solvent is supplied to the reactor at a constant supply rate, and a polymerization liquid is withdrawn in an amount corresponding to the supply amount of the monomer mixture. If necessary, a polymerization initiator can be added to the monomer mixture, and the amount of the initiator added is preferably 0.001 to 2 parts by weight per 100 parts by weight of the monomer mixture. The pressure depends on the reaction temperature and the boiling points of the monomer mixture and the solvent used, and may be any pressure that does not affect the reaction but can maintain a predetermined reaction temperature. The residence time of the monomer mixture is preferably 1 to 60 minutes. If the residence time is less than 1 minute, the monomers may not react sufficiently, and if the residence time exceeds 60 minutes, the productivity may decrease. The preferred residence time is 2 to 40 minutes.
[0028] Examples of the polymerization initiator used to obtain the copolymer (a1) may be any initiator that generates radicals at a predetermined reaction temperature. Specifically, examples include organic peroxides such as di-t-butyl peroxide, di-t-hexyl peroxide, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, cumene hydroperoxide, and t-butyl hydroperoxide, and azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), azobiscyclohexacarbonitrile, azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-amidinopropane)dihydrochloride, and 4,4'-azobis(4-cyanovaleric acid). The polymerization initiator may be used alone or in combination of two or more of these.
[0029] The amount of the polymerization initiator used can be appropriately adjusted depending on the types of polymerization initiator and monomer, the desired molecular weight, polymerization conditions, etc., but is generally 0.001 to 10 parts by weight per 100 parts by weight of the monomer used.
[0030] When an organic solvent is used for producing the copolymer (a1), an organic hydrocarbon compound is suitable, and examples thereof include cyclic ethers such as tetrahydrofuran and dioxane, aromatic hydrocarbon compounds such as benzene, toluene and xylene, esters such as ethyl acetate and butyl acetate, ketones such as acetone, methyl ethyl ketone and cyclohexanone, and alcohols such as methanol, ethanol and isopropanol, and one or more of these can be used. Organic solvents that do not dissolve the (meth)acrylate copolymer well tend to cause scale growth on the walls of the reactor, which can lead to production problems in the cleaning process and the like.
[0031] The amount of the organic solvent used is preferably 80 parts by weight or less based on 100 parts by weight of the total vinyl monomers. By using 80 parts by weight or less, a high conversion rate can be obtained in a short time. More preferably, it is 1 to 50 parts by weight. In addition, a dehydrating agent such as trimethyl orthoacetate or trimethyl orthoformate can also be added. In producing the copolymer (a1), a known chain transfer agent may be used.
[0032] The reaction liquid discharged from the reactor can be directly used for the next step, or the polymer can be isolated by removing volatile components such as unreacted monomers, organic solvents, and low molecular weight oligomers by distillation, etc. A part of the volatile components such as unreacted monomers, organic solvents, and low molecular weight oligomers distilled off from the reaction liquid can be returned to the raw material tank or directly to the reactor, and can be reused in the polymerization reaction. The method of recycling the unreacted monomers and the organic solvent is economically preferable. When recycling, it is necessary to determine the mixing ratio of the monomer mixture to be newly fed so as to maintain the desired monomer ratio and the desired amount of the organic solvent in the reactor.
[0033] (1-5) Physical properties of copolymer (a1) The weight average molecular weight (hereinafter also referred to as "Mw") of the copolymer (a1) is usually 1500 to 50000, preferably 1500 to 40000, more preferably 2000 to 30000, even more preferably 2500 to 25000, and particularly preferably 3000 to 15000. By having an Mw of 50000 or less, the obtained component (A) can be made to have a low viscosity even at a relatively high concentration, improving the coatability, and also improving the compatibility when mixed with other curable resins. By having an Mw of 1500 or more, the obtained cured product of the component (A) has excellent weather resistance and tensile properties. In the present invention, Mw means a value obtained by converting the molecular weight measured by gel permeation chromatography (hereinafter referred to as GPC) into polystyrene equivalent.
[0034] The glass transition temperature (hereinafter referred to as "Tg") of the copolymer (a1) is not particularly limited, but is usually from -40°C to 90°C, and preferably from 0°C to 90°C. A temperature of 0°C or higher leads to a cured product with excellent strength, and a temperature of 90°C or lower leads to a cured product with excellent flexibility. A temperature of 30 to 80°C is more preferable.
[0035] In the present invention, Tg means a value determined from the intersection of the tangent line at the inflection point and the baseline of a heat flux curve obtained using a differential scanning calorimeter such as TA Instrument (Q-100). The heat flux curve is obtained under the following conditions: about 10 mg of a sample is cooled to -100°C in a nitrogen atmosphere, held for 5 minutes, heated to 300°C at 10°C / min, cooled to -100°C, held for 5 minutes, and heated to 350°C at 10°C / min.
[0036] In the case of a typical solution polymerization method such as that disclosed in JP2014-115538A, the polymerization temperature is relatively low, and therefore the number of functional groups is biased for each polymer molecule due to the influence of the copolymerization reactivity ratio. On the other hand, in the case of high-temperature polymerization, the influence of the copolymerization reactivity ratio is low, and in the case of continuous polymerization, a constant polymer continues to be produced, so the bias in the number of functional groups for each molecule is extremely small. In addition, when comparing normal solution polymerization with high-temperature polymerization, when synthesizing a polymer of the same molecular weight, high-temperature polymerization requires less polymerization initiator and leaves less initiator residue, resulting in better weather resistance. In particular, in the case of electron beam curing, since no polymerization catalyst such as a photoinitiator is used in the curing reaction, the amount of initiator residue contained in the polymer significantly affects weather resistance. Therefore, the copolymer (a1) used in the present invention generally has a terminal double bond concentration of 0.5 meq / g or less, and more preferably 0.4 meq / g or less. When the terminal double bond concentration is 0.5 meq / g or less, the decrease in the curing rate can be suppressed. In addition, in the present invention, when a copolymer obtained by high-temperature continuous polymerization is used as the copolymer (a1), the terminal double bond concentration of the copolymer (a1) is preferably 0.02 meq / g or more and 0.5 meq / g or less. By being 0.02 meq / g or more, rapid curing during curing is suppressed, and residual stress is less likely to remain, resulting in improved mechanical properties.
[0037] (2) Unsaturated compound (a2) The unsaturated compound (a2) is a compound having an acryloyl group and a group reactive with the reactive group of the copolymer (a1). As described above, the component (A) is obtained by reacting the reactive group in the copolymer (a1) obtained by the polymerization method etc. with the reactive group of the unsaturated compound (a2). More specifically, the component (A) is obtained by chemically bonding and adding the unsaturated compound (a2) to the copolymer (a1) having the reactive group via the reactive group.
[0038] When the copolymer (a1) has an epoxy polymer or a hydroxyl group as the reactive group, the unsaturated compound (a2) can be a compound having a carboxyl group or an isocyanate group as a functional group that reacts with the reactive group. Examples of the unsaturated compound (a2) having a carboxyl group include acrylic acid, acrylic acid dimer, a γ-butyrolactone adduct of acrylic acid, and a δ-valerolactone adduct of acrylic acid. Other specific examples include an ε-caprolactone adduct of acrylic acid. An adduct of acrylic acid with ε-caprolactone is commercially available, and an example of such an adduct is Aronix M-5300 (trade name, manufactured by Toagosei Co., Ltd.; polycaprolactone chain length ≈ 2).
[0039] Examples of the unsaturated compound (a2) having an isocyanate group include 2-(acryloyloxy)ethyl isocyanate and urethane acrylate having an isocyanate group at one end. The urethane acrylate having an isocyanate group at one end can be produced by reacting a diol with a diisocyanate to produce a compound having isocyanate groups at both ends, and then reacting this with a hydroxyl group-containing acrylate. In this case, the diisocyanate can be isophorone diisocyanate or hexamethylene diisocyanate, and the diol can be polytetramethylene glycol. The hydroxyl group-containing acrylate can be 2-hydroxyethyl acrylate. Examples of methods for producing the compound include a method in which a diisocyanate and a diol are reacted in an organic solvent in the presence of a tin catalyst such as dioctyltin to obtain a compound having isocyanate groups at both ends, and then a hydroxyl group-containing acrylate is reacted in the presence of a polymerization inhibitor.
[0040] When the copolymer (a1) is a copolymer having an isocyanate group or a carboxyl group as the reactive group, the unsaturated compound (a2) may be a compound having a hydroxyl group as a functional group that reacts with the reactive group. Examples of the unsaturated compound (a2) having a hydroxyl group include hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 3-hydroxybutyl acrylate, and 4-hydroxybutyl acrylate. Other specific examples include an ε-caprolactone adduct of 2-hydroxyethyl acrylate, a polypropylene glycol adduct of acrylic acid, a polyethylene glycol adduct of acrylic acid, a poly(3-hydroxybutyrate) adduct of 2-hydroxyethyl acrylate, and a polytetramethylene glycol adduct of acrylic acid. These ε-caprolactone adducts of 2-hydroxyethyl acrylate are commercially available, and examples thereof include Plaxel FA5 (trade name manufactured by Daicel Corporation; the same applies below) and Plaxel FA2D (molecular weight 344).
[0041] Of these compounds, the unsaturated compound (a2) is preferably an acrylate oligomer, and more preferably an acrylate oligomer having a Tg of -30 to -90°C when cured. In the present invention, the oligomer means a compound having a molecular weight of 250 or more and 2,000 or less. An example of an acrylate oligomer having a carboxyl hydroxyl group is an ε-caprolactone adduct of acrylic acid. An adduct of acrylic acid with ε-caprolactone is commercially available, and an example thereof is ARONIX M-5300 (trade name, manufactured by Toagosei Co., Ltd.; Tg=−78° C., polycaprolactone chain length≈2). Examples of acrylate oligomers having a hydroxyl group include an ε-caprolactone adduct of 2-hydroxyethyl acrylate, a polypropylene glycol adduct of acrylic acid, a polyethylene glycol adduct of acrylic acid, a poly(3-hydroxybutyrate) adduct of 2-hydroxyethyl acrylate, and a polytetramethylene glycol adduct of acrylic acid. Adducts of 2-hydroxyethyl acrylate with ε-caprolactone are commercially available, including Plaxel FA2D (Tg=−78° C.). An example of a polypropylene glycol adduct of acrylic acid is a compound having a Tg of -75°C, an example of a polyethylene glycol adduct of acrylic acid is a compound having a Tg of -41°C, an example of a poly(3-hydroxybutyrate) adduct of 2-hydroxyethyl acrylate is a compound having a Tg of -40°C, and an example of a polytetramethylene glycol adduct of acrylic acid is a compound having a Tg of -84°C. Examples of the acrylate oligomer (a2) having an isocyanate group include urethane acrylates having an isocyanate group at one end.
[0042] (3) Production method of component (A) The component (A) is preferably produced by reacting a reactive group of the copolymer (a1) with a group in the unsaturated compound (a2) that is reactive with the reactive group. That is, examples of the reaction for adding the above-mentioned unsaturated compound (a2) to the copolymer (a1) include a method of reacting the copolymer (a1) having an epoxy group or a hydroxyl group as a reactive group with the unsaturated compound (a2) having a carboxyl group, and a method of reacting the copolymer (a1) having an isocyanate group or a carboxyl group as a reactive group with the unsaturated compound (a2) having a hydroxyl group.
[0043] The reaction ratio of the copolymer (a1) and the unsaturated compound (a2) may be appropriately set depending on the type of the component (A) to be produced, etc. The amount of the reactive group in the unsaturated compound (a2) is preferably 0.5 to 1.5 mol, more preferably 0.8 to 1.2 mol, and further preferably 0.9 to 1.1 mol, per 1 mol of the reactive group in the copolymer (a1).
[0044] As a method for reacting and adding the unsaturated compound (a2) having a carboxyl group to the copolymer (a1) having an epoxy group, there can be mentioned a method in which the copolymer (a1) having an epoxy group, the unsaturated compound (a2) having a carboxyl group, a catalyst, and a solvent are mixed and heated to 60 to 120°C for about 5 to 30 hours.
[0045] The reaction ratio of the copolymer (a1) having an epoxy group and the unsaturated compound (a2) having a carboxyl group is preferably 0.5 to 1.5 mol, more preferably 0.8 to 1.2 mol, and even more preferably 0.9 to 1.1 mol of the carboxyl group of the unsaturated compound (a2) having a carboxyl group per 1 mol of the epoxy group of the copolymer (a1) having an epoxy group.
[0046] Examples of the catalyst include tetrabutylammonium bromide, tetrabutylammonium chloride, tetramethylammonium bromide, tetramethylammonium chloride, triphenylphosphine, tributylphosphine, 1,8-diazabicyclo[5,4,0]-7-undecene, and 1,4-diazabicyclo[2,2,2]octane. Among these, triphenylphosphine is preferably used because it causes less coloring of the cured product after a heat resistance test.
[0047] The amount of the catalyst added is preferably about 0.5 to 5% by weight based on the total amount of the copolymer (a1) having an epoxy group and the unsaturated compound (a2) having a carboxyl group.
[0048] Examples of the organic solvent include ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, etc. When the copolymer (a1) having an epoxy group is in a liquid state, the modification reaction can be carried out without adding an organic solvent.
[0049] The method of reacting the copolymer (a1) having a hydroxyl group with the unsaturated compound (a2) having a carboxyl group includes a general dehydration esterification method, which includes a method of heating the copolymer (a1) having a hydroxyl group, the unsaturated compound (a2) having a carboxyl group, a catalyst, and a solvent in a mixed state at 100 to 120°C, and azeotropically dehydrating the solvent and the water produced to proceed with the reaction.
[0050] Examples of the catalyst include p-toluenesulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid and sulfuric acid. The amount of the catalyst used is 0.05 to 5 mol % based on the number of moles of hydroxyl groups to be reacted.
[0051] As the solvent, it is preferable to use an organic solvent that has low solubility in water generated in the dehydration esterification reaction and allows the reaction to proceed while distilling off water by azeotropy. Preferred organic solvents include, for example, aromatic hydrocarbons such as toluene, benzene, and xylene, aliphatic hydrocarbons such as hexane, cyclohexane, and heptane, and ketones such as methyl ethyl ketone and cyclohexanone. The proportion of the solvent is preferably 30 to 70% by weight based on the total amount of the reaction liquid.
[0052] After the reaction, the acid is generally removed with water or an aqueous alkali solution.
[0053] As a method for reacting and adding the unsaturated compound (a2) having a hydroxyl group to the copolymer (a1) having an isocyanate group, there can be mentioned a method in which the copolymer (a1) having an isocyanate group is mixed with the unsaturated compound (a2) having a hydroxyl group, and then, if necessary, a curing catalyst such as dibutyltin dilaurate is added and the mixture is heated to 60 to 100°C.
[0054] As a method of reacting and adding the unsaturated compound (a2) having a hydroxyl group to the copolymer (a1) having a carboxyl group, there can be mentioned a method in which the copolymer (a1) having a carboxyl group and the unsaturated compound (a2) having a hydroxyl group are mixed, and then a catalyst such as sulfuric acid, methanesulfonic acid, p-toluenesulfonic acid, sulfonated polystyrene, Nafion-H or the like is added, and optionally the mixture is heated to 80 to 120°C in the presence of an organic solvent such as toluene to proceed with the esterification reaction while distilling off the water produced. Furthermore, the catalyst remaining after the reaction can be removed by one or a combination of two or more of the following methods: washing with water, alkali neutralization, ion exchange resins, chemical filters for catalyst removal, and filtration.
[0055] In any of the above modification methods, it is preferable to add a polymerization inhibitor for the purpose of suppressing gelation or for the purpose of improving the storage stability of the modified product, component (A). Examples of the polymerization inhibitor include methoxyphenol, hydroquinone, dibutylhydroxytoluene, etc. From the viewpoint of suppressing coloration of the cured product, it is particularly preferable to use dibutylhydroxytoluene.
[0056] (4) Physical properties of component (A) (acrylic equivalent and molecular weight)> The acrylic equivalent of component (A) is preferably 3000 g / eq or less, more preferably 150 g / eq or more and 2500 g / eq or less, even more preferably 300 g / eq or more and 2000 g / eq or less, even more preferably 400 g / eq or more and 1400 g / eq or less, and particularly preferably 700 g / eq or more and 1000 g / eq or less. By setting the acrylic equivalent to 150 g / eq or more, the elongation and flexibility of the cured product can be ensured, and by setting it to 3000 g / eq or less, the strength and weather resistance of the cured product can be ensured and a good curing speed can be maintained.
[0057] In the present invention, the acrylic equivalent (g / eq) represents the weight (g) per equivalent (eq) of acryloyl groups, and the larger the value, the lower the concentration of acryloyl groups, and the smaller the value, the higher the concentration of acryloyl groups.
[0058] The acrylic equivalent can be calculated by the following formula: In the following formula, the number of moles of acryloyl groups in component (A) is the number of moles of acryloyl groups in the unsaturated compound (a2) added to the copolymer (a1) in the above modification reaction, and does not include acryloyl groups derived from the unreacted unsaturated compound (a2) present after the above modification reaction.
[0059]
number
[0060] The molecular weight, Mw, of component (A) is preferably from 2,000 to 60,000, and more preferably from 2,000 to 50,000. By having Mw of 2,000 or more, the cured product has excellent weather resistance and tensile properties, and by having Mw of 60,000 or less, the viscosity can be reduced even at a relatively high concentration, resulting in excellent coatability and excellent compatibility when mixed with other curable compounds. The Mw of component (A) is more preferably 3,000 to 40,000, even more preferably 30,000 to 30,000, and even more preferably 4,000 to 20,000. The number average molecular weight (hereinafter referred to as "Mn") of component (A) is preferably 1,000 to 30,000. When Mn is 1,000 or more, the cured product has excellent weather resistance and tensile properties, and when Mn is 30,000 or less, the viscosity can be reduced even at a relatively high concentration, resulting in excellent coatability and excellent compatibility when mixed with other curable compounds. The Mn of component (A) is more preferably 1,500 to 15,000, even more preferably 2,000 to 10,000, and even more preferably 2,500 to 7,000. In the present invention, Mn means a value calculated by converting the molecular weight measured by GPC into polystyrene equivalent value.
[0061] 2. Water-dispersible active energy ray curable composition The present invention relates to a water-dispersed active energy ray-curable composition comprising component (A) dispersed in water, wherein the content of an organic solvent in the total amount of the composition is less than 5% by weight. The component (A) may be dispersed in water in a conventional manner.
[0062] (1) Aqueous conversion When the reaction between the copolymer (a1) and the unsaturated compound (a2) is carried out in an organic solvent, the reaction may then be made aqueous to give an aqueous dispersion of the component (A). The aqueous solution may be prepared, for example, by adding water (hereinafter also referred to as "component (B)") and a surfactant (dispersant) (hereinafter also referred to as "component (C)") to the organic solvent solution of component (A) obtained by the above reaction, stirring and mixing to disperse component (A) in water, and then removing the organic solvent by heating under reduced pressure. In this case, it is necessary to remove the solvent until the content of the organic solvent is less than 5% by weight, preferably less than 3% by weight, and more preferably less than 1.5% by weight.
[0063] As another method for making the component (A) aqueous, water (component (B)) and component (C) can be added to component (A) which has been isolated in advance, and the mixture can be stirred. When component (A) is a mixed liquid containing an organic solvent, the organic solvent is generally removed by heating under reduced pressure or distillation, as described above.
[0064] Furthermore, if component (A) (or its organic solvent mixture) is insoluble in water, the modified product may precipitate even when water and component (C) are added, the uniformity of the system may not be maintained, and a homogeneous dispersion may not be obtained. In such a case, a water-soluble organic solvent (hereinafter also referred to as "component (D)") can be added before or simultaneously with the addition of water [component (B)] and component (C) to form an aqueous dispersion, and then component (D) can be removed by distillation.
[0065] As the component (C), various emulsifiers such as anionic emulsifiers, nonionic emulsifiers, cationic emulsifiers, and zwitterionic emulsifiers can be used. Examples of the anionic emulsifier include dialkyl sulfosuccinates, alkylbenzene sulfonates, alkyl sulfates, polyoxyethylene alkyl phenyl ether sulfates, polyoxyethylene alkyl diphenyl ether sulfates, polyoxyethylene alkyl ether sulfates, alkyl diphenyl ether disulfonates, and polymer emulsifiers. Examples of nonionic emulsifiers include polyoxyethylene higher alcohol ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene alkyl diphenyl ethers, polyoxyethylene-polyoxypropylene block copolymers, acetylene diol-based emulsifiers, sorbitan higher fatty acid esters, polyoxyethylene sorbitan higher fatty acid esters, polyoxyethylene higher fatty acid esters, glycerin higher fatty acid esters, polycarboxylic acid-based polymer emulsifiers, polyvinyl alcohol, and the like. Cationic emulsifiers include alkyl(amido)betaines, alkyldimethylamine oxides, and the like. As the component (C), one type may be used alone, or two or more types may be used in combination. Of these emulsifiers, nonionic surfactants are particularly preferred as component (C).
[0066] The addition ratio of component (C) is preferably 0.5 to 15 parts by weight, more preferably 1 to 10 parts by weight, and even more preferably 2 to 7 parts by weight, in terms of the pure content of component (C) per 100 parts by weight of component (A), or per 100 parts by weight of the total amount of components (A) and (E) in the case where component (E) described below is contained. By making the component (C) 0.5 parts by weight or more, it is possible to improve the dispersion stability, and by making it 15 parts by weight or less, the water resistance of the cured product will be improved.
[0067] Examples of the component (D) include alkyl alcohols having 1 to 4 carbon atoms, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, sec-butyl alcohol, and tert-butyl alcohol; amides such as dimethylformamide, dimethylacetamide, etc., ketones or ketoalcohols such as acetone, and diacetone alcohol; Ethers such as tetrahydrofuran and dioxane, polyalkylene glycols such as polyethylene glycol and polypropylene glycol; Alkylene glycols in which the alkylene group contains 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, 1,2-hexanediol, 1,2,6-hexanetriol, thiodiglycol, hexylene glycol, and diethylene glycol; lower alkyl ethers of polyhydric alcohols such as glycerin, ethylene glycol monomethyl (or ethyl) ether, diethylene glycol methyl (or ethyl) ether, and triethylene glycol monomethyl (or ethyl) ether; Pyrrolidones such as N-methyl-2-pyrrolidone and 2-pyrrolidone; and 1,3-dimethyl-2-imidazolidinone and the like.
[0068] As component (D), the above compounds can be used alone or in combination of two or more kinds, as necessary.
[0069] (2) Other components The composition of the present invention can contain various components depending on the purpose. Preferred components include an ethylenically unsaturated compound other than component (A) (hereinafter also referred to as "component (E)"), and a photopolymerization initiator (hereinafter also referred to as "component (F)"). In addition to the above components, additives such as dispersants, antifoaming agents, viscosity adjusters, thickeners, leveling agents, sagging prevention agents, pigments, pH adjusters, crosslinking agents, plasticizers, stabilizers, preservatives, antifungal agents, antifreeze agents, film-forming assistants, solvents, antibacterial agents, antioxidants, light stabilizers, and ultraviolet absorbers may be added. When a pigment is blended in the composition, it is preferable to further blend a dispersant, and a dispersant for aqueous systems is more preferable. Examples of dispersants for aqueous systems include the compounds listed above as examples of component (C). Among these, neutralized salts of amines or ammonia of carboxyl group-containing polymers, which are polycarboxylic acid-based polymer emulsifiers, are particularly preferred. Specific examples of polycarboxylic acid-based polymer emulsifiers include commercially available products such as FLOWLEN G-700AMP (manufactured by Kyoeisha Chemical Co., Ltd.), FLOWLEN GW-1640 (manufactured by Kyoeisha Chemical Co., Ltd.), NOPCOL 5200 (manufactured by San Nopco Ltd.), NOPCOSPERSE 6100 (manufactured by San Nopco Ltd.), DISPERBYK-190 (manufactured by BYK Chemie), DISPERBYK-180 (manufactured by BYK Chemie), and DISPERBYK-2010 (manufactured by BYK Chemie). Components (E) and (F) will be described below.
[0070] (2-1) Component (E) The composition of the present invention may contain, as necessary, component (E), an ethylenically unsaturated compound other than component (A), for the purpose of reducing the viscosity of the entire composition or adjusting other physical properties.
[0071] Specific examples of component (E) include monomer (a1-1), monomer (a1-2), (meth)acrylates other than monomers (a1-1) and (a1-2) [hereinafter referred to as "other (meth)acrylates"], and N-vinyl-2-pyrrolidone.
[0072] Examples of the monomer (a1-1) and the monomer (a1-2) include the same compounds as those mentioned above.
[0073] Other examples of (meth)acrylates include compounds having one (meth)acryloyl group (hereinafter referred to as "monofunctional (meth)acrylates") and compounds having two or more (meth)acryloyl groups (hereinafter referred to as "polyfunctional (meth)acrylates").
[0074] Specific examples of monofunctional (meth)acrylates include trimethylcyclohexyl (meth)acrylate, 1-adamantyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, benzyl (meth)acrylate, allyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, o-phenylphenol EO-modified (n=1 to 4) (meth)acrylate, p-cumylphenol EO-modified (n=1 to 4) (meth)acrylate, phenyl (meth)acrylate, o-phenylphenyl (meth)acrylate, p-cumylphenyl (meth)acrylate, N-(meth)acryloylmorpholine, N-vinylformamide, N-(meth)acryloyloxyethyl hexahydrophthalimide, and N-(meth)acryloyloxyethyl tetrahydrophthalimide.
[0075] Specific examples of polyfunctional (meth)acrylates include urethane (meth)acrylates such as urethane acrylates having a polyester skeleton, and urethane (meth)acrylates such as urethane acrylates having a polycarbonate skeleton; Di(meth)acrylates having a bisphenol skeleton, such as bisphenol A EO-modified (n=1 to 2) di(meth)acrylate and bisphenol A di(meth)acrylate; (Poly)alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol (n=5-14) di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol (n=5-14) di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, polybutylene glycol (n=3-16) di(meth)acrylate, and poly(1-methylbutylene glycol) (n=5-20) di(meth)acrylate. Di(meth)acrylates of aliphatic diols, such as 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; Hydroxypivalic acid neopentyl glycol di(meth)acrylate; Di(meth)acrylates having an alicyclic skeleton, such as tricyclodecanedimethylol di(meth)acrylate; (Meth)acrylates with an isocyanurate skeleton, such as EO-modified isocyanuric acid diacrylate and ε-caprolactone-modified tris((meth)acryloxyethyl)isocyanurate Polyol poly(meth)acrylates such as glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri- or tetra(meth)acrylate, ditrimethylolpropane tri- or tetra(meth)acrylate, diglycerin tri- or tetra(meth)acrylate, and dipentaerythritol tri-, tetra-, penta- or hexa(meth)acrylate; and Examples of the poly(meth)acrylate include polyol alkylene oxide adducts such as tri(meth)acrylate of a glycerin alkylene oxide adduct, tri- or tetra(meth)acrylate of a pentaerythritol alkylene oxide adduct, tri- or tetra(meth)acrylate of a ditrimethylolpropane alkylene oxide adduct, tri- or tetra(meth)acrylate of a diglycerin alkylene oxide adduct, and tri-, tetra-, penta- or hexa(meth)acrylate of a dipentaerythritol alkylene oxide adduct. In the above, EO-modified means ethylene oxide-modified, and n means the number of repeating alkylene oxide units. Among these compounds, the polyfunctional (meth)acrylate is preferably a urethane (meth)acrylate or a (meth)acrylate having an isocyanate skeleton.
[0076] As the component (E), the above-mentioned compounds may be used alone or in combination of two or more.
[0077] The blending ratio of component (E) may be appropriately set depending on the purpose, and may be any amount that does not reduce the flexibility of the obtained cured product. However, the blending ratio of component (E) is preferably 1 to 70 parts by weight, more preferably 1 to 50 parts by weight, and even more preferably 1 to 25 parts by weight, per 100 parts by weight of the total amount of components (A) and (E).
[0078] (2-2) Component (F) When ultraviolet light and visible light are used as the active energy rays, the composition of the present invention may contain component (F) (photopolymerization initiator). When electron beams are used as the active energy rays, it is not always necessary to incorporate component (F), but a small amount of component (F) can be incorporated as necessary to improve curability.
[0079] Component (F) may be benzil dimethyl ketal, benzil, benzoin, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, oligo[2-hydroxy-2-methyl-1-[4-1-(methylvinyl)phenyl]propanone, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methyl- aromatic ketone compounds such as 2-methyl-1-[4-(methylthio)]phenyl-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)butan-1-one, ADEKA Optomer N-1414 (manufactured by ADEKA Corporation), phenylglyoxylic acid methyl ester, ethyl anthraquinone, and phenanthrenequinone; benzophenone compounds such as benzophenone, 2-methylbenzophenone, 3-methylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, 4-phenylbenzophenone, 4-(methylphenylthio)phenylphenylmethane, methyl-2-benzophenone, 1-[4-(4-benzoylphenylsulfanyl)phenyl]-2-methyl-2-(4-methylphenylsulfonyl)propan-1-one, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, N,N'-tetramethyl-4,4'-diaminobenzophenone, N,N'-tetraethyl-4,4'-diaminobenzophenone and 4-methoxy-4'-dimethylaminobenzophenone; Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, ethyl-(2,4,6-trimethylbenzoyl)phenylphosphinate and bis(2,6-dimethoxybenzo acylphosphine oxide compounds such as (yl)-2,4,4-trimethylpentylphosphine oxide; Thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 1-chloro-4-propylthioxanthone, 3-[3,4-dimethyl-9-oxo-9H-thioxanthone-2-yl]oxy]-2-hydroxypropyl-N,N,N-trimethylammonium chloride and fluorothioxanthone; Acridone compounds such as acridone and 10-butyl-2-chloroacridone; Oxime esters such as 1,2-octanedione 1-[4-(phenylthio)-2-(O-benzoyloxime)] and ethanone 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime); 2,4,5-triarylimidazole dimers such as 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-phenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer, 2,4-di(p-methoxyphenyl)-5-phenylimidazole dimer and 2-(2,4-dimethoxyphenyl)-4,5-diphenylimidazole dimer; and Examples of the acridine derivatives include 9-phenylacridine and 1,7-bis(9,9'-acridinyl)heptane.
[0080] These compounds can be used alone or in combination of two or more.
[0081] The blending ratio of component (F) is preferably 0.01 to 10 parts by weight, and more preferably 0.1 to 5 parts by weight, per 100 parts by weight of component (A) in the case where component (E) is included, and per 100 parts by weight of the total amount of components (A) and (E). By setting the blending ratio of component (F) to 0.01 parts by weight or more, the composition can be cured with an appropriate amount of ultraviolet or visible light, improving productivity, while by setting the blending ratio to 10 parts by weight or less, the cured product can have excellent weather resistance and transparency.
[0082] (3) Regarding the composition The composition of the present invention is a composition in which component (A) is dispersed in water, or a composition which further contains the above-mentioned other components which are blended as necessary. The proportion of component (A) in the composition, or, when other components are further contained, the total proportion of component (A) and other components, may be adjusted so as to obtain a viscosity suitable for use, but the composition preferably contains 15 to 60% by weight, more preferably 20 to 50% by weight, and even more preferably 20 to 40% by weight, as solids. The viscosity of the composition may be appropriately set depending on the method of use, and for example, when applying with an applicator, it is preferably 500 to 30,000 mPas, more preferably 1,000 to 15,000 mPas. If the viscosity is too low, dripping is likely to occur after application, and if the viscosity is too high, the finished appearance will be poor. In the case of spray coating, it is preferably 50 to 1,000 mPas, more preferably 100 to 500 mPas. In the present invention, the viscosity refers to a value measured at 25° C. using an E-type viscometer (cone-plate type viscometer).
[0083] (4) Physical properties of the cured product The composition of the present invention exhibits the effect that the cured product thereof has excellent tensile properties such as tensile strength and elongation, as well as excellent weather resistance. In terms of tensile properties, the breaking strength is preferably 4 MPa or more, more preferably 15 MPa or more, and particularly preferably 30 MPa or more. Next, the elongation is preferably 2% or more. The tensile product is preferably 50 MPa or more. Since breaking strength and elongation are generally in a trade-off relationship, the higher the tensile product (breaking strength x elongation / 2), the better the tensile properties.
[0084] 3. Method of use The water-dispersible active energy ray-curable composition of the present invention can be used in various ways depending on the purpose. For example, when the composition of the present invention is used as a coating agent, the composition can be applied to a substrate, heated to evaporate water in the composition, and then irradiated with active energy rays to cure the composition. When the composition of the present invention is used as an adhesive, the composition can be applied to a substrate, heated to evaporate water in the composition, and then laminated to another substrate, and then irradiated with active energy rays to cure the composition.
[0085] The composition of the present invention can be applied to a variety of substrates, including inorganic materials, plastics, and paper. Inorganic materials include glass, metal, mortar, concrete, and stone. Examples of metals include steel sheets, metals such as aluminum and chromium, and metal oxides such as zinc oxide (ZnO) and indium tin oxide (ITO). Specific examples of plastics include polyolefins such as polyethylene and polypropylene, ABS resins, polyvinyl alcohol, cellulose acetate resins such as triacetyl cellulose and diacetyl cellulose, acrylic resins, polyethylene terephthalate (hereinafter referred to as "PET resins"), polycarbonates, polyarylates, polyethersulfones, cyclic polyolefin resins having cyclic olefins as monomers such as norbornene, polyvinyl chloride, epoxy resins, polyurethane resins, etc. Thermoplastic plastics are preferred, and specific examples thereof include PET resins, acrylic resins, ABS resins, polycarbonates, polypropylene, polyethylene, etc., with PET resins being preferred. Of these materials, metals and plastics are preferred as the substrate. The shape of the substrate is not particularly limited, and may be any of a sheet, film, plate, and the like.
[0086] The method for applying the composition may be appropriately selected depending on the purpose, and examples of the method include coating using a conventional bar coater, applicator, doctor blade, knife coater, comma coater, reverse roll coater, die coater, lip coater, gravure coater, and microgravure coater.
[0087] The composition of the present invention is a water-dispersed composition and may contain a small amount of organic solvent. After application to a substrate, it is preferable to heat and dry the composition to evaporate the water and / or the organic solvent. The drying temperature is not particularly limited as long as it is a temperature below which the substrate to be applied does not cause problems such as deformation. A preferred heating temperature is 40 to 100° C. The drying time may be appropriately set depending on the substrate to be applied and the heating temperature, and is preferably 0.5 to 20 minutes.
[0088] The thickness of the cured film of the composition on the substrate may be appropriately set depending on the purpose. The thickness of the cured film may be selected depending on the substrate to be used and the application of the substrate having the produced cured film, but is preferably 1 to 100 μm, more preferably 2 to 40 μm.
[0089] Examples of the active energy ray used to cure the active energy ray-curable composition of the present invention include electron beam (EB), ultraviolet ray (UV), and visible light. Of these, ultraviolet light is preferred since it can be cured using a relatively simple device and can be cured with low-energy irradiation in a short time. Electron beam irradiation is preferred because it is not necessary to add component (F) (photopolymerization initiator) and the cured product has excellent heat resistance and weather resistance. When the composition of the present invention contains a large amount of pigment or ultraviolet absorber, ultraviolet light will deteriorate the curing property, so electron beam irradiation is suitable. Examples of ultraviolet irradiation devices include high-pressure mercury lamps, metal halide lamps, ultraviolet (UV) electrodeless lamps, and light-emitting diodes (LEDs).
[0090] In the case of active energy ray irradiation, the irradiation conditions such as the dose, irradiation amount, irradiation intensity, etc. may be appropriately selected depending on the composition used, the base material, the purpose, etc. As an example of using ultraviolet light, when using a high-pressure mercury lamp, the irradiation energy in the UV-A region is 100 to 8,000 mJ / cm 2 is preferable, and 200 to 3,000 mJ / cm 2 is more preferred. When an electron beam is used, it is preferable to irradiate with an acceleration voltage of 50 to 300 kV and an absorbed dose of 10 to 1,000 kGy.
[0091] The water-dispersible active energy ray-curable composition of the present invention can be used for various applications. Specific examples thereof include coating agents, adhesives, inks, and films, and the like, and the material can be preferably used as a coating agent. Specific applications of the coating agent include decorative films and topcoats for vehicle exterior parts. EXAMPLES
[0092] The present invention will be described in more detail below with reference to examples and comparative examples. In the following, "parts" means parts by weight. In the Production Examples and Working Examples, the molecular weight, Tg, acid value, solids content, (meth)acrylic equivalent, and amount of residual volatile components were measured according to the following methods.
[0093] <Molecular weight measurement> The polystyrene-equivalent weight average molecular weight (Mw) and number average molecular weight (Mn) were obtained using a gel permeation chromatograph (model number "HLC-8320", manufactured by Tosoh Corporation) under the following conditions. Measurement conditions Column: Tosoh Corporation TSKgel SuperMultiporeHZ-M x 4 Column temperature: 40℃ Eluent: Tetrahydrofuran Detector: RI
[0094] <Measurement of Tg> The Tg of the copolymer (a1) was measured by a differential scanning calorimeter (DSC) under the following conditions. Measurement conditions DSC: TA Instrument (Q-100) Temperature rise: 10℃ / min Measurement atmosphere: Nitrogen
[0095] <Measurement of acid value> The acid value measurement was carried out according to JIS K0070. That is, the sample was weighed out so that the titration amount was about 10 mL, and diluted with about 50 mL of tetrahydrofuran, and then titration was carried out using an automatic titration device COM-1600ST (manufactured by Hiranuma Sangyo Co., Ltd.) with a 0.1 N KOH / ethanol solution as the titrant.
[0096] <Solid content> The solid content was determined from the weight loss by drying in a ventilated dryer at 150°C for 1 hour.
[0097] <(Meth)acrylic equivalent> The weight (g) of the raw materials used excluding the organic solvent component was divided by the number of moles of the compound having a reactive group and a (meth)acryloyl group used to obtain the (meth)acrylic equivalent (g / eq). In the examples, a compound having a methacryloyl group may be used as a comparative example, and is expressed as a (meth)acrylic equivalent.
[0098] <Measurement of the amount of residual volatile components> Residual isopropyl alcohol (IPA) and residual butyl acetate were measured by gas chromatography. (Gas chromatograph measurement conditions) Gas chromatograph: GC390 (GL Sciences) Column: CP-WAX52CB (Agilent Technologies) Carrier gas: Nitrogen gas (1.9 mL / min) Injection temperature: 220℃ Detector temperature: 230℃ Oven temperature: 40℃ x 5 min, increase temperature at 7℃ / min, hold at 230℃ x 5 min. -Creating a calibration curve Accurately weigh out 0.02 g of each of the components to be measured (standards) and isobutyl acrylate (internal standard) and dissolve them in acetone (5 mL). Measure this mixture by gas chromatography to determine the detection sensitivity of each component relative to the internal standard. ·measurement 1 g of the aqueous dispersion and 0.02 g of isobutyl acrylate were precisely weighed and dissolved in acetone (10 mL). This mixture was subjected to gas chromatography to calculate the amount of residual volatile components contained in the polymer. Detection limit for each component: 0.05% by weight
[0099] 1. Production examples (1) Production example 1 (Preparation of (meth)acrylate polymer A-1 having acryloyl groups in the side chains) The temperature of a 1000 mL pressurized stirred tank reactor equipped with an oil jacket was kept at 188° C. Next, while keeping the pressure of the reactor constant, a monomer mixture consisting of 70 parts of methyl methacrylate (hereinafter referred to as “MMA”), 10 parts of ethyl acrylate (hereinafter referred to as “EA”), 20 parts of glycidyl methacrylate (hereinafter referred to as “GMA”), 12 parts of methyl ethyl ketone (hereinafter referred to as “MEK”) as a solvent, 3 parts of trimethyl orthoacetate (manufactured by Nippoh Chemicals, trade name “MOA”, hereinafter referred to as “MOA”), and 1 part of di-t-hexyl peroxide (manufactured by NOF Corp., trade name “Perhexyl D”, hereinafter referred to as “DTHP”) as a polymerization initiator was continuously fed from a raw material tank to the reactor at a constant feed rate (48 g / min, residence time: 12 min), and a reaction liquid equivalent to the amount of the monomer mixture fed was continuously withdrawn from the outlet. Immediately after the start of the reaction, the reaction temperature dropped once, and then a temperature rise due to the heat of polymerization was observed, but the reaction temperature was maintained at 187 to 189°C by controlling the temperature of the oil jacket.
[0100] The point at which the temperature stabilized after the start of the monomer mixture supply was set as the start point for collecting the reaction liquid, and the reaction was continued for 37 minutes from this point, resulting in 1.78 kg of monomer mixture being supplied and 1.78 kg of reaction liquid being collected. The reaction liquid was then introduced into a thin-film evaporator, and volatile components such as unreacted monomers were separated to obtain 1.08 kg of a (meth)acrylate polymer having an epoxy group (hereinafter referred to as "copolymer a-1").
[0101] Next, copolymer a-1 (100 parts), dibutylhydroxytoluene (hereinafter referred to as "BHT") (0.11 parts) as a polymerization inhibitor, acrylic acid (hereinafter referred to as "AA") (11.2 parts, corresponding to an acid value of 1.05 equivalents of the epoxy group of polymer a-1), and butyl acetate (47.9 parts) as an organic solvent were placed in a 1 L flask, and the liquid temperature was raised to 95°C while bubbling a 5% oxygen-nitrogen mixed gas, to dissolve polymer a-1. After uniform dissolution, triphenylphosphine (hereinafter referred to as "TPP") (0.56 parts) was added as a reaction catalyst, and the mixture was stirred for 12 hours while maintaining the internal temperature at 95°C. Further, TPP (0.56 parts) was added, and the mixture was reacted for 12 hours. After that, the acid value was measured, and it was confirmed to be 3.6 mg KOH / g, and the reaction was terminated. As a result, a butyl acetate solution containing polymer A-1, which is an AA adduct (acrylate modified product) of copolymer a-1, was obtained.
[0102] Table 1 shows the solids content, acid value, polystyrene-equivalent Mn (number average molecular weight) and Mw (weight average molecular weight), and (meth)acrylic equivalent (g / eq) of the polymer A-1 solution.
[0103] (2) Production examples 2 to 10, Comparative production example 1 Except for changing the conditions as shown in Table 1, the same procedure as in Production Example 1 was carried out to obtain (meth)acrylate polymers A-2 to 10 and A'-1 having an acryloyl group in the side chain. In addition, M-5300 in Table 1 is as defined below.
[0104] (3) Production example 11 A (meth)acrylic polymer having an isocyanate group (hereinafter, referred to as "copolymer a-9") was obtained by the same procedure as in Production Example 1, except that the conditions were changed as shown in Table 1. The MOI in Table 1 is as defined below. Then, copolymer a-9 (100 parts), dibutylhydroxytoluene (0.12 parts) as a polymerization inhibitor, 2-hydroxyethyl acrylate (hereinafter referred to as "HEA") (24.7 parts, equivalent to a hydroxyl value of 1.0 equivalent of the isocyanate group of polymer a-9), dibutyltin dilaurate (0.03 parts) as a catalyst, and butyl acetate (64.3 parts) were placed in a 1 L flask, and the liquid temperature was raised to 80°C while bubbling a 5% oxygen-nitrogen mixed gas, to dissolve copolymer a-9. The mixture was stirred for 6 hours while maintaining the temperature at 80°C, and the reaction was terminated when it was confirmed using an ATR infrared spectrophotometer (Spectrum100 manufactured by Perkin Elmer) that the absorption at 2200 cm-1 due to isocyanate had disappeared. As a result, a butyl acetate solution containing polymer A-11, which is an HEA adduct (acrylate modified product) of copolymer a-9, was obtained.
[0105] (4) Production example 12 Polymer A-12, which is an FA-2D adduct (acrylate modified product) of copolymer a-9, was obtained by the same procedure as in Production Example 11 except that the conditions were changed as shown in Table 1. In addition, FA-2D in Table 1 is as defined below.
[0106] (5) Comparative production example 2 Polymer A'-2, which is an MOI adduct (acrylate modified product) of copolymer a'-2, was obtained by the same procedure as in Production Example 11 except that the conditions were changed as shown in Table 1.
[0107] [Table 1]
[0108] The abbreviations in Table 1 have the following meanings. Note that, in the following, some of the abbreviations already defined above are repeated. MMA: Methyl methacrylate ·BA: Butyl acrylate ·EA: Ethyl acrylate GMA: Glycidyl methacrylate MOI: 2-isocyanate ethyl methacrylate (Karens MOI (product name), manufactured by Showa Denko K.K.) HEMA: 2-hydroxyethyl methacrylate ·AA: Acrylic acid MEK: Methyl ethyl ketone MOA: Trimethyl orthoacetate (MOA (trade name), manufactured by Nippoh Chemicals) DTHP: Di-t-hexyl peroxide (Perhexyl D (trade name), manufactured by NOF Corp.) M5300: ε-caprolactone adduct of acrylic acid [Aronix M-5300 (trade name), manufactured by Toagosei Co., Ltd., average degree of polymerization of caprolactone: 2, number average molecular weight: 300, Tg: -78°C, acid value: 186 mgKOH / g] ·HEA: 2-Hydroxyethyl acrylate FA-2D: ε-caprolactone adduct of 2-hydroxyethyl acrylate (Placcel FA2D (trade name), manufactured by Daicel Corporation, average degree of polymerization of caprolactone: 2, number average molecular weight: 344, Tg: -78°C, hydroxyl value: 163 mgKOH / g) TPP: Triphenylphosphine ·DBTDL: Dibutyltin dilaurate BHT: Dibutyl hydroxytoluene
[0109] 2. Examples (UV curable composition) (1) Example 1 The polymer A-1 solution obtained in Production Example 1 (140.8 parts, containing 100 parts of polymer A-1), component (F) 1-hydroxycyclohexyl-phenyl ketone [Omnirad184 manufactured by IGM Resins BV] (3 parts), and component (D) isopropyl alcohol (hereinafter referred to as "IPA") (150 parts) were placed in a 3L flask and mixed. Next, component (C) nonionic surfactant [polyoxyethylene styrenated phenyl ether, HLB value: 17.5, 60% aqueous solution, Noigen EA-197D manufactured by Daiichi Kogyo Seiyaku Co., Ltd., hereinafter referred to as "197D)] (10 parts) and component (B) ion-exchanged water (250 parts) were added and mixed. The mixture was heated to 80° C. with stirring, and the pressure was reduced to 20 kPa to remove volatile matter. When 240 parts of the volatile matter had been removed, IPA (50 parts) and ion-exchanged water (200 parts) were added. Further, 251 parts of the volatile matter was removed under reduced pressure to obtain a water dispersion of polymer A-1. Table 2 shows the solid content, the remaining IPA, and the remaining butyl acetate in the aqueous dispersion. The obtained UV-curable composition, which was a water dispersion of polymer A-1, was evaluated by the following methods. The results are shown in Table 2.
[0110] (2) Examples 2 to 15, Comparative examples 1 to 3 Except for changing the conditions shown in Table 2, the same procedure as in Example 1 was carried out to obtain ultraviolet-curable compositions which were aqueous dispersions of the polymers A-2 to A-12, A'-1, A'-2 and M1200. Table 2 shows the solid content, the remaining IPA, and the remaining butyl acetate in the aqueous dispersion. The curability, tensile properties and weather resistance of the resulting UV-curable composition, which was an aqueous dispersion of the polymer, were evaluated by the following methods. The results are shown in Table 2.
[0111] <Evaluation of curability> Cosmoshine A-4300 (trade name, Toyobo's easy-adhesive PET film, thickness: 50 μm) was prepared as a base film, tape was attached to both ends, and the composition obtained in the above examples and comparative examples was applied to the surface of the base film using a bar coater #0 so that the film thickness after drying was 50 to 60 μm. Then, it was dried in a ventilated dryer at 90° C. for 10 minutes to obtain a coated film having a dried coating film of the composition. Next, a high-pressure mercury lamp manufactured by Eye Graphics Co., Ltd. was used in an air atmosphere, with a concentrated UVA irradiance of 500 mW / cm 2 , the irradiation dose per time is 500mJ / cm 2 The applied film was passed once under the light irradiation on a conveyor. The coated film and the obtained cured film were subjected to IR measurement before and after irradiation using an ATR infrared spectrophotometer (Spectrum 100 manufactured by Perkin Elmer). 1730cm -1 For acryloyl compounds, the absorbance is 810 cm -1 Calculate the relative absorbance value (for methacryloyl compounds, 940 cm -1 The reaction rate after irradiation was calculated according to the following formula, assuming that the reaction rate of the (meth)acryloyl group before irradiation was 0%. The reflectance is preferably 70% or more.
[0112]
number
[0113] <Evaluation of tensile physical properties> Lumirror T-60 (product name, PET film manufactured by Toray Industries, Inc., film thickness: 100 μm) was prepared as a base film, tape was attached to both ends of the film, and the composition obtained in the above Examples and Comparative Examples was applied to the surface of the base film using a bar coater #0 so that the film thickness after drying was 60 to 80 μm. The film was then dried at 90° C. for 10 minutes in a forced air dryer to obtain a coated film having a dried coating film of the composition. Next, using the same high-pressure mercury lamp as in the curing evaluation, in an air atmosphere, the UVA irradiance was 500 mW / cm 2 , the irradiation dose per session is 800mJ / cm 2 The applied film was passed twice under the light irradiation on a conveyor. Next, the coated film was cut into a 1 cm wide strip, and the cured film was peeled off from the substrate film. The breaking elongation (%) and breaking strength (unit: MPa) of this cured film were measured at a tensile speed of 5 mm / min using a tensile tester (Autograph AGS-J, manufactured by Shimadzu Corporation). The tensile product was calculated using the following formula. Tensile product = breaking strength x elongation / 2
[0114] <Evaluation of weather resistance> Zeonor ZF14-100 (product name, cycloolefin polymer manufactured by Zeon Corporation, film thickness: 100 μm) was prepared as a substrate film, tape was attached to both ends, and the composition obtained in the above Examples and Comparative Examples was applied to the surface of the substrate film using a bar coater #0 so that the film thickness after drying was 50 to 60 μm. Then, it was dried at 90° C. for 10 minutes in a ventilated dryer to obtain a coated film having a dried coating film of the composition. Next, using the same high pressure mercury lamp as in the evaluation of curability, the coated film was passed twice on a conveyor under the same light irradiation conditions as in the evaluation of tensile properties. Next, the film having the cured layer obtained by UV irradiation was placed in a metal weather meter (DAIPLA METAL WEATHER KU-R5NCI-A (product name) manufactured by Daipla Wintes Co., Ltd.) and subjected to an accelerated weather resistance test. The irradiation conditions were 63°C, 70% RH, and illuminance of 80 mW / cm. 2 The test was conducted for 300 hours with a two-minute shower once every two hours. The evaluation was based on the color difference and haze before and after the test.
[0115] <Measurement of color difference> The yellowness index (YI) was measured using a spectrophotometer SE-2000 (product name) manufactured by Nippon Denshoku Industries Co., Ltd. (YI is calculated according to the following formula). ΔYI is preferably 3.5 or less. YI = 100(1.28X-1.06Z) / Y (X, Y, Z are color coordinates) ΔYI = YI-YI0 (YI0 indicates YI before the test) (Haze measurement) Measurement was performed using NDH2000 (product name) manufactured by Nippon Denshoku Industries Co., Ltd., and the difference in haze (Δ haze) before and after the test was evaluated. Δ haze is preferably 7.0 or less.
[0116] [Table 2]
[0117] 3. Examples (Electron beam curable composition) (1) Examples 16 to 30, Comparative examples 4 to 6 Except for not blending the component (F), the composition was made water-based in the same manner as in Examples 1 to 15 and Comparative Examples 1 to 3, to obtain electron beam curable compositions which were water dispersions of each polymer. Table 3 shows the solid content, the remaining IPA, and the remaining butyl acetate of the electron beam curable composition which is a water dispersion. The obtained electron beam curable composition was used to evaluate the curability by the following method, and the tensile properties and weather resistance were evaluated by the same methods as described above. The results are shown in Table 3. The electron beam irradiation conditions in the evaluation of the tensile properties and weather resistance were also the same as those in the evaluation of the curability described below.
[0118] <Evaluation of curability> A coated film was prepared in the same manner as in the case of the above ultraviolet-curable composition. The resulting coated film was irradiated with electron beams using an electron beam irradiation device manufactured by NHV Corporation under conditions of an acceleration voltage of 150 kV, a dose of 150 kGy (adjusted by beam current and transport speed), and an oxygen concentration of 300 ppm or less. The curability was evaluated in the same manner as for the ultraviolet-curable composition.
[0119] [Table 3]
[0120] The abbreviations in Tables 2 and 3 have the following meanings: M1200: Non-yellowing polyester-based urethane acrylate (Mw=4,500) [Aronix M-1200 (product name), manufactured by Toagosei Co., Ltd.] M5300: ε-caprolactone adduct of acrylic acid [Aronix M-5300 (trade name), manufactured by Toagosei Co., Ltd., average degree of polymerization of caprolactone: 2, number average molecular weight: 300, Tg: -78°C, acid value: 186 mgKOH / g] Omnirad184: 1-Hydroxycyclohexyl-phenyl ketone [Omnirad184 (trade name), manufactured by IGM Resins BV] IPA: Isopropyl alcohol 197D: Nonionic surfactant (polyoxyethylene styrenated phenyl ether, HLB value: 17.5, 60% aqueous solution) [Noigen EA-197D (trade name), manufactured by Daiichi Kogyo Seiyaku Co., Ltd.]
[0121] 4. Summary of results In the case of the ultraviolet-curable compositions shown in Table 2 (Examples 1 to 15, Comparative Examples 1 to 3), the polymers having methacryloyl groups as side chains in Comparative Examples 1 and 2 had low reactivity, poor curability, and also poor tensile properties and weather resistance. In contrast, the polymers having acryloyl groups as side chains in Examples 1 to 15 had high reactivity, excellent curability, and were able to achieve both tensile properties and weather resistance. Among the examples, the polymers modified with a high molecular weight acrylate oligomer such as M5300 were superior in tensile properties (especially elongation) to the polymers modified with a low molecular weight compound such as acrylic acid. In comparing the molecular weights of component (A) (Examples 5, 8, 9, and 10), there was an optimum point in terms of tensile properties, with Example 5 being the best. In a comparison of the acrylic equivalents of component (A) (Examples 5, 11, and 12), Examples 5 and 11 were superior in weather resistance to Example 12, which had a large acrylic equivalent (low acrylic concentration). The electron beam curable compositions (Examples 16 to 30, Comparative Examples 4 to 6) shown in Table 3 show roughly the same tendency as the ultraviolet ray curable compositions. However, when comparing the ultraviolet ray curable compositions with the electron beam curable compositions, the electron beam curable compositions were superior in terms of weather resistance (especially haze). [Industrial Applicability]
[0122] The water-dispersible active energy ray-curable composition of the present invention is excellent in curability, substantially contains no solvent, and has low environmental impact. The cured product thereof can be suitably used in fields that require a cured product having excellent mechanical strength, heat resistance, and weather resistance, and can be utilized in fields such as adhesives, coating agents, inks, films, etc.
Claims
1. A water-dispersible active energy ray-curable composition comprising a (meth)acrylate polymer (A) [hereinafter referred to as "component (A)"] having an acryloyl group in a side chain, the component (A) being dispersed in water, wherein the content of an organic solvent in the total amount of the composition is less than 5 wt %, and the acrylic equivalent of component (A) is 3000 g / eq or less.
2. 2. The water-dispersible active energy ray-curable composition according to claim 1, wherein the component (A) is a reaction product of a copolymer (a1) (hereinafter referred to as "copolymer (a1)") having a structural unit derived from a (meth)acrylate monomer (a1-1) having no reactive group and a structural unit derived from a (meth)acrylate monomer (a1-2) having a reactive group, and a compound (a2) (hereinafter referred to as "unsaturated compound (a2)") having a group reactive with the reactive group and an acryloyl group.
3. The water-dispersible active energy ray-curable composition according to claim 2, wherein the (meth)acrylate monomer (a1-2) having a reactive group constituting the copolymer (a1) is a (meth)acrylate monomer having a reactive group selected from the group consisting of an epoxy group, a carboxyl group, a hydroxyl group, and an isocyanate group.
4. 4. The water-dispersible active energy ray-curable composition according to claim 2, wherein the unsaturated compound (a2) is an acrylate oligomer having a glass transition temperature (Tg) of -30 to -90°C.
5. The water-dispersible active energy ray-curable composition according to any one of claims 1 to 4, comprising the component (A) in an amount of 15 to 60% by weight based on the total amount of the composition.
6. 6. The water-dispersible active energy ray-curable composition according to claim 1, wherein the active energy ray is an electron beam.
7. A curable composition for use as a coating agent, comprising the composition according to any one of claims 1 to 6.
8. A method for producing a water-dispersed active energy ray-curable composition, comprising mixing and dispersing a (meth)acrylate polymer (A) having an acryloyl group in a side chain and an acrylic equivalent of 3000 g / eq or less, a surfactant (C) and a water-soluble organic solvent (D) in water, and then heating under reduced pressure to reduce the organic solvent content in the total composition to less than 5 weight %.
Citation Information
Patent Citations
Energetic ray curing coating composition
JP1983025365A
Photocurable resin composition and coating material
JP1992366178A
Production of aqueous reactive resin dispersion
JP1998195142A
Water-base ultraviolet-curable ink composition
JP1998195361A
Water-base ultraviolet-curable overprint varnish composition
JP1998195371A